Core Muscle Activation With Foam Rolling and Static Planks - Zahiri, Ali; Alizadeh, Shahab; Daneshjoo, Abdolhamid; Pike, Nick; Konrad, Andreas; Behm, David G. (Frontiers in Physiology, 2022)
The objective of this study was to compare the activation of the core (trunk) musculature during quadriceps and hamstrings foam rolling (FR) versus prone and supine/reverse static planks to determine if FR is a viable means of training the core musculature. Using a randomized allocation, nine recreationally trained, young adults (18-26 years) performed two sets each of quadriceps and hamstrings FR as well as supine/reverse and prone static planks for 30-s each with 1-min rest between sets and 5-min rest between exercises. Electromyographic (EMG) activity of the lower abdominals (LA), external obliques (EO), lumbosacral erector spinae (LSES), upper lumbar erector spinae (ULES) muscle groups were normalized to a maximum voluntary contraction and analyzed. Quadriceps FR exhibited a very large magnitude greater LA activity compared to reverse plank (p=0.033, d=4.42) and hamstrings FR (p=0.020, d=3.49) respectively. The prone plank demonstrated very large magnitude higher EO EMG activity compared to reverse plank (p=0.001, d=9.17), hamstrings FR (p=0.002, d=8.14), and quadriceps FR (p=0.011, d=5.97). Reverse plank (p=0.003, d=12.06), and quadriceps FR (p=0.002, d=7.84) induced greater ULES activity compared to the prone plank and hamstrings FR respectively. Reverse plank also exhibited very large magnitude higher LSES activity compared to the prone plank (p<0.001, d=7.68), hamstrings FR (p=0.002, d=4.11), and quadriceps FR (p=0.005, d=2.34), respectively. In conclusion, whereas reverse plank was the most effective activator of dorsal core muscles, quadriceps FR may also be a time efficient alternative exercise to induce back muscle activation. The prone plank is effective for ventral core muscles activation.